An ontology roadmap for crowdsourcing innovation intermediaries - Silva, Cândida (2015)
Ontologies have proliferated in the last years, essentially justified by the need of achieving a consensus in the multiple representations of reality inside computers, and therefore the accomplishment of interoperability between machines and systems. Ontologies provide an explicit conceptualization that describes the semantics of the data. Crowdsourcing innovation intermediaries are organizations that mediate the communication and relationship between companies that aspire to solve some problem or to take advantage of any business opportunity with a crowd that is prone to give ideas based on their knowledge, experience and wisdom, taking advantage of web 2.0 tools. Various ontologies have emerged, but at the best of our knowledge, there isn’t any ontology that represents the entire process of intermediation of crowdsourcing innovation. In this paper we present an ontology roadmap for developing crowdsourcing innovation ontology of the intermediation process. Over the years, several authors have proposed some distinct methodologies, by different proposals of combining practices, activities, languages, according to the project they were involved in. We start making a literature review on ontology building, and analyse and compare ontologies that propose the development from scratch with the ones that propose reusing other ontologies. We also review enterprise and innovation ontologies known in literature. Finally, are presented the criteria for selecting the methodology and the roadmap for building crowdsourcing innovation intermediary ontology.